La invención del arquitecto - Bonilla Di Tolla, Enrique (2015)
Although architecture has always existed, architects have not. There are records o architects, especially from greco-roman antiquity, but they disappear into the Middle Ages. During the renaissance, architecture is defined as an artistic and scientific discipline. In addition to that, the architect was invented —in a platonic view— as demiurge or maker of architecture itself. The first text that talks about architecture and architects is the work of Vitruvius, but with Leon Battista Alberti, significant figure within the creation of the architect, that the importance of architecture and architects is specified within the construct of the human culture.